(3TQM GdTeSjIs - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J(B793(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO GdPj HUQfG HfhQ GdgOGjI hHYO abO SCdfj aQbI ef NdGfj Cf CTQM dge GdQSGdI GdTeSjI bOGM GdfXQ aj TQM GdaGVd bWH GdOjf GdQGRjs
(3BNQgG (B:s
(3haj GdEYOGO HGdYOOjI hCeG Ydi hLg GdYehe adG jYJO Hg aj GdUfGYI hdG jLYd ef GdBKGQ GdeWdhHI HGdGJaGb hdjcJa HgPG hdjca gPG GdbOQ ef eHGMK GdehVhYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 219s
(3eYLe GdeDdajf (B3 / 849s
(3cTa GdXfhf (B2 / 1063s
(3TPQGJ GdPgH (B6 / 319s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs